Re‐introducing whole blood for transfusion: considerations for blood providers. Issue 2 (30th September 2020) - Hervig, Tor A.; Doughty, Heidi A.; Cardigan, Rebecca A.; Apelseth, Torunn O.; Hess, John R.; Noorman, Femke; Bohoněk, Miloš; Yazer, Mark H.; Lu, Jia; Wendel, Silvano; Sparrow, Rosemary L.
Abstract : Whole blood is the original blood preparation but disappeared from the blood bank inventories in the 1980s following the advent of component therapy. In the early 2000s, both military and civilian practice called for changes in the transfusion support for massive haemorrhage. The 'clear fluid' policy was abandoned and replaced by early balanced transfusion of platelets, plasma and red cells. Whole blood is an attractive alternative to multi‐component therapy, which offers reduced hemodilution, lower donor exposure and simplified logistics. However, the potential for wider re‐introduction of whole blood requires re‐evaluation of haemolysins, storage conditions and shelf‐life, the need for leucocyte depletion/ pathogen reduction and inventory management for blood providers. This review addresses these questions and calls for research to define the optimal whole blood product and the indications for its use.